The Effect Of Efficiency And Security On Customer Interest In Transactions With Mobile Banking At PT Bank Sumut - Syawitri, Faramila; Juli Meliza (Jurnal Ekonomi, 2024)
The aim of this research is to determine the influence of efficiency and security on interest in making transactions using mobile banking at PT Bank Sumut KCP Sisingamangaraja. This type of research is quantitative research. The population in this study was all 800 customers of PT Bank Sumut KCP Sisingamangaraja in 2016-2019. The research sample used a random sampling method. The data collection method in this research is through a questionnaire. The analytical method used in this research is the Descriptive Analysis method and Multiple Linear Regression Analysis. Based on the results of the F test, it shows that Efficiency and Security together have a positive effect on Transaction Interest. Based on the t-test results, it shows that efficiency has a positive effect on transaction interest. Security has a positive and significant effect on Transaction Interest. Based on the value of the Coefficient of Determination (Adjusted R-square), it can be seen that Efficiency and Security influence Interest in Transactions with Mobile Banking by 0.702 or 70.2%, while the remaining 29.8% is influenced by other factors outside those studied by researchers.